2017
DOI: 10.1007/s00394-017-1587-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary iodine concentration and thyroid hormones: Korea National Health and Nutrition Examination Survey 2013–2015

Abstract: This first nationwide study in Korea demonstrated that the median of UIC and estimated iodine intake lie at nearly 300 µg/L and 250 µg/day, respectively, which shows an overall excellent iodine nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…This study demonstrated that the median UIC varied with age but not with geographic location. A recent study with subjects aged 20 years and older also reported that the median UIC decreased according to age, supporting our data . We also found that the median adjusted UIC varied by age and geographic location although we did not find various regularities between UIC and adjusted UIC.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study demonstrated that the median UIC varied with age but not with geographic location. A recent study with subjects aged 20 years and older also reported that the median UIC decreased according to age, supporting our data . We also found that the median adjusted UIC varied by age and geographic location although we did not find various regularities between UIC and adjusted UIC.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies reported the relationship between UIC and thyroid functions . A Korean study reported that the serum TSH and FT4 levels showed statistically significant as UIC . The prevalence of clinical hypothyroidism, subclinical hypothyroidism, and positive thyroid antibodies, assessed with UIC, was significantly higher in individuals with more than adequate iodine intake, than in individuals with adequate iodine intake .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties with food eaten outside of the home were also reported by people in Brazil [20]. Experiences may be different in the UK, since the typical Korean diet is very high in iodine [21] and in Brazil salt is iodised [20]. However, there was anecdotal evidence that people in the UK had found LID advice confusing and difficult to follow before the UK LID-WG released the standardised diet sheet [15].…”
Section: Discussionmentioning
confidence: 99%
“…These items are generally based on existing baccalaureate curricula, on the learning objectives of major subjects for nursing, and on specifications outlined for the Korean Nursing Licensing Examination [1,2,3,4]. However, there is a need to transition from items that not only test rote learning skills and understanding of curricula to those that also test problem-solving skills using real-life clinical case studies and a nurse’s ability to interpret and apply the knowledge needed to perform the nursing role [5].…”
Section: Introductionmentioning
confidence: 99%